Comparative Analysis Of Religious Aspects In Children Aged 5 To 6 Years - Siti, Masganti; Wilujeng, Aprilia (Literacy: Journal of Education and Social Science, 2023)
The development of religious values is the ability of children to behave and behave. Religious development in children aged 5 to 6 years is a complex process and is influenced by various factors. Parents and educators have an important role in helping children to understand and practice their religious teachings. Islam has taught positive values that are useful in community life. The results of the analysis show that in Islamic teachings it has been explained how the process of developing religious values in early childhood can be applied correctly. The results of the analysis through discussion found 10 important methods for the development of religious values in children aged 5 to 6 years, including: storytelling, singing, poetry, tourism works, habituation, playing, outbound, role playing, discussion, and example. The findings have been discussed with various concepts and previous findings.